INTERNAL COMMUNICATION MANAGEMENT AND COMMUNICATION BARRIERS WITHIN ORGANIZATIONS (A Case Study at the Leadership and Managerial Training Center) - Hikmawansyah, Muhammad Agus; Mulyana, Ahmad (Universitas Mercu Buana, 2025)
Communication is an integral part of the daily functioning of any organization. However, in practice, communication does not always run smoothly. There are communication barriers within organizations that can hinder the creation of effective communication. The Leadership and Managerial Training Center (Pusat Pendidikan dan Pelatihan Kepemimpinan dan Manajerial/Pusdiklat KM) is a unit tasked with organizing training in leadership and managerial fields. In leadership and managerial competencies, communication, both interpersonal and organizational, plays a crucial role. This study examines how Pusdiklat KM manages communication within its organization and explores the communication barriers that occur. The approach used in this study is qualitative with a case study method. Data were obtained through in-depth interviews with key informants, followed by triangulation through confirmation or cross-checking with relevant parties. The data were then analyzed using Weber's Bureaucracy Theory and Elton Mayo's Human Relations Theory, linked to communication barriers as mentioned by DeVito and Chruden and Sherman. The research findings indicate that internal communication management at Pusdiklat KM is not in the form of a structured communication management but rather focuses on utilizing all available communication channels and methods to create mutual understanding. Pusdiklat KM, which has an organizational structure with tasks and functions that do not interrelate, faces challenges in its internal communication. Technical, human, and semantic communication barriers were identified, including barriers due to communication media, differences in personality, lack of emotional closeness, high workload, and varying leadership competencies.